PENINGKATAN KEMAMPUAN GURU AGAMA HINDU DALAM MENGANALISIS PENETAPAN KKM MELALUI MGMP DI KABUPATEN GIANYAR - Made Adnyana (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
This study aims to determine the increase in the ability of Hindu religious teachers in analyzing the determination of the KKM through MGMPs Gianyar regency. This research is a school action (PTS) using two design cycles and each cycle consists of four phases: planning - action - observation - reflection. To get the research data used in the form of a test measurement techniques to obtain quantitative data and observation sheet to obtain qualitative data. Data were analyzed using descriptive analysis. Based on the results of studies conducted in two cycles of the first cycle and the second cycle, the results are as follows: First, at the end of the implementation of the first and second cycle there is an average increase teachers’ ability to analyze the results of the determination of the KKM through MGMPs in Gianyar amounting to 11.14 from the previous training of 75.00 into 86.14 after the second cycle executed on your skill level religious teachers Hindu achieve high grades. Second, it turns out upgrading of Hindu religious teachers analyze Determination KKM through MGMPs in Gianyar showed a very significant outcome of the initial conditions before the training. It turned out that the training of teachers through MGMPs very useful to improve the competence of teachers to increase the confidence in carrying out his duties as an educator.